Effects of paddy price support withdrawal on Malaysian rice sector: time series econometric approach - Umar, Haruna Suleiman; Abdullah, Amin Mahir; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin (Asian Economic and Social Society, 2014)
The study simulated effects of paddy price support withdrawal, as an alternative policy, on key variables namely domestic rice supply, domestic rice demand, net import of rice, area planted to paddy and paddy producer price. Time series data (1980-2012) were collected and analyzed using Autoregressive Distributed lag (ARDL). The long run coefficients or elasticities generated were used in scenarios simulation through appropriate simulation technique. The results show that, on the average, paddy price support withdrawal would affect the rice sector by 2020 in the following ways: 13% decline in domestic rice production; 23% increase in net rice import; area planted to paddy decrease in size by 13%; and, paddy producer price reduce by 20%. However, there was no effect on aggregate rice consumption. Since the country is concern about raising farm income and ensuring rice food security, sustaining the paddy support price is worthwhile policy in order to avoid a decline in paddy producer price (income) and surge in import bills.